INVESTIGATING DEMOTIVATING FACTORS OF EFL TEACHERS WHEN TEACHING ENGLISH - Shannon, Jesicca Levina (Journal of English Language and Culture, 2025)
Motivation is essential in teaching and learning; it drives us to work persistently to reach a specific goal. However, only a few studies have explored possible demotivating factors in English as a Foreign Language (EFL) teachers when they teach English effectively. As a response, this study aims to explore what causes demotivation in EFL teachers when teaching English and how they should deal with that demotivation effectively. To meet the research objectives, the researcher first conducted a comprehensive literature review of 18 articles published in national (indexed in SINTA 1 & 2) and international journals. Then, the researcher interviewed 4 lecturers to discuss the literature review analysis results thoroughly. The research found that heavy workloads, burnout, and low salaries were the main factors that could increase demotivation in teaching. Meanwhile, teachers’ engagement in school activities and their relationships with students were identified as helpful strategies for maintaining or restoring motivation, suggesting that these interpersonal and institutional or restoring motivation, suggesting that these interpersonal and institutional connections can act as ways to cope with demotivating factors. The data collected from the interviews with the lecturers mostly contrast with that which has been found in previous studies. Most of the answers from the interviews contrasting with the previous studies related to the interviewees’ genuine passion for teaching as a profession. Directions for further research and practical implications are presented.